Comparisons of performances for determining the relative importance in the modern pentahlon - Lee, S.-H.; Park, J.-C.; Kim, K.-B.; Kim, S.-J.; Ko, B.-G. (Korean Journal of Sport Science, 2020)
Purpose: The purpose of this study was to compare the official world records of UIPM in the last 3 years to find out the relationship between the score characteristics of fencing, swimming, equestrian, and laser-run events in the final rankings and to analyze the relative importance of each event.